Lump on Back: A Rare Case of Parosteal Lipoma of Scapula - Ankit Balani; Ashwini Sankhe; Tilak Dedhia; Maunil Bhuta; Narayan Lakhotia; Jagir Yeshwante (Case Reports in Radiology)
Lipomas are benign tumors of mature adipose tissue which can occur in subcutaneous, intramuscular, intermuscular, parosteal, and intraosseous compartments. Parosteal lipoma is a rare type of lipoma, accounting for less than 0.1% of primary bone neoplasms and 0.3% of all lipomas. Parosteal lipomas commonly arise in the femur and extremities. Around 150 cases have been reported in English literature with scapula being a rare site of involvement. They are known to be associated with underlying bony changes like focal cortical hyperostosis, pressure erosion of the underlying bone, and bowing deformity or with underlying osteochondroma. We report a rare case of a parosteal lipoma arising in the scapula with a bony excrescence in a 38-year-old male.